A história da geometria nos livros didáticos e perspectivas do PNLD - Pimentel, Guilherme Henrique (2012)
The purpose of this research is to analyze ways to approach the history of mathematic text books in 9th grade in elementary school. For this we take as the documents mathematics textbooks listed by Plano Nacional do Livro Didático (PNLD). The PNLD is a public policy that is effective and follows the Parâmetros Curriculares Nacionais (PCN), select, purchase and distribute textbooks throughout the country for all levels of education. Among the requirements of the PNLD is the inclusion of the history of mathematics that can be used as a means to achieve the contextualization and interdisciplinary suggested by official documents. The textbooks are understood as symbolic forms so that this analysis context and allow a look at the approach that relates the history of mathematics in the textbook with the current situation of education in the country. The research is qualitative in that it performs content analysis on the themes of history textbooks in geometry. The analyzes indicate that the textbooks try on the one hand, serve the PNLD and include the history of mathematics, but do not reach the intended objectives and are lacking as to whether this approach with regard to problem solving, developing content and interdisciplinary, which is predominantly informative history of mathematics and use, for example, charges that in addition to distort, can present a contrast between the idealization of the genius scientist and the demystification of the same. And then, on the one hand for the PCN, PNLD intends reconfigurations in the educational field, on the other, the school and textbooks are still organized in a linear manner and discipline. Changes perceived by the analysis of textbooks from different periods of history are more significant in terms of significant changes to graphics, also provided by technological advances in the publishing field. On the one hand, current textbooks that address various aspects of the proposed PCN, since they were selected through PNLD, it is clear that contextualization and interdisciplinary is somewhat superficial, or are somehow present, but not so structural rather than aggregated as the traditional organization. From the point of view of content, books remain the same adding the incentive for new methodologies and items to bring more than illustrations, historical information, challenges, games etc. The content itself and your thread have not changed significantly.